1981
DOI: 10.1079/bjn19810037
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fibre sources on aflatoxicosis in the weanling male rat

Abstract: 1.Two experiments with mal: weanling rats were conducted in which they received individually and restrictedly either a basal semi-purified diet containing starch as the principal carbohydrate or the same diet to which mixed aflatoxins were added in quantities providing from 0-1 3 to 0.4mg aflatoxin BJkg diet. Various natural ingredients, or semi-purified sources of dietiry fibre were substituted for a portion of the starch in the basal diet containing aflatoxin. The diets were fed fcr 13-14 weeks after which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In addition, the excretion of AFM 1 was reduced as compared with rats receiving the starch‐rich diet . Conversely, rats receiving diets containing a greater amount of starch retained more C‐labelled AFB 1 in the liver, suggesting an influence of carbohydrate on the absorption, excretion and liver retention of AFB 1 . This is supported by another study in which Wistar rats administered 400 µg kg −1 AFB 1 and manno‐oligosaccharides showed clear liver tissue damage and signs of toxicity .…”
Section: Effect Of Carbohydrate and Caloric Restriction On Aflatoxicomentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, the excretion of AFM 1 was reduced as compared with rats receiving the starch‐rich diet . Conversely, rats receiving diets containing a greater amount of starch retained more C‐labelled AFB 1 in the liver, suggesting an influence of carbohydrate on the absorption, excretion and liver retention of AFB 1 . This is supported by another study in which Wistar rats administered 400 µg kg −1 AFB 1 and manno‐oligosaccharides showed clear liver tissue damage and signs of toxicity .…”
Section: Effect Of Carbohydrate and Caloric Restriction On Aflatoxicomentioning
confidence: 95%
“…However, the influence of carbohydrate on aflatoxicosis is not well understood. A study found that partial substitution of dietary starch (principal carbohydrate source) mixed with AFB 1 by other sources of dietary fiber caused an apparent reduction in tumor incidence in male rats . In addition, the excretion of AFM 1 was reduced as compared with rats receiving the starch‐rich diet .…”
Section: Effect Of Carbohydrate and Caloric Restriction On Aflatoxicomentioning
confidence: 99%
See 1 more Smart Citation
“…A previous investigation demonstrated that the faecal excretion of 14C by rats given 14C-labelled aflatoxin B, orally was increased when a part of their dietary starch was replaced by wheat offal (Frape et al 1981). There are several mechanisms by which such an effect might be achieved.…”
mentioning
confidence: 99%
“…In two of four experiments previously reported (Frape et al 1981) the intestinal absorption, retention and excretion of 14C-labelled aflatoxin was measured over a period of several days following a single dose in rats receiving wheat offal or gum arabic in their diet. The purpose of the experiments to be described was to investigate the distribution of 14C radioactivity in male rats relatively soon after an oral dose of 14C-labelled aflatoxin B, and to measure how this distribution might be influenced by replacing a portion of the dietary starch by wheat offal or gum arabic.…”
mentioning
confidence: 99%